A highly-efficient exciplex-based multifunctional fluorescent film probe to aniline and N-methylphenethylamine vapors. (February 2023) - Liu, Guangjuan; Li, Jiaqi; Zhang, Houyu; Wang, Yue; Zhang, Ming
Abstract: Exciplexes are often mentioned in the research of organic light-emitting diode (OLED), but there are nearly no reports using the ready-made exciplexes as fluorescent probes directly. In this work, F1 based on the fluorescent exciplex composed of 4, 4′, 4″- tris (N-carbazolyl) triphenylamine (TCTA) and 1- phenyl- 1H- benzo[d]imidazole −1, 3, 5- triazine (PIM-TRZ) is firstly applied as fluorescent film probe to organic amine vapors. The F1 film can accurately identify aniline (AN) and N-methylphenethylamine (MPEA, a simulant of methamphetamine) vapors, as well as roughly distinguish aliphatic and aromatic amine vapors easily by different output signals: the AN vapor causes an instantaneous and entire fluorescence quenching, MPEA vapor leads to the fluorescence quenching of the F1 film along with obvious red-shifted photoluminescence (PL) spectrum, the common aliphatic amine vapors bring the emergence of emission peak of TCTA, and the common aromatic amine vapors only result in partial fluorescence quenching of the F1 film. To the best of our knowledge, it is the first multifunctional fluorescent probe to highly identify AN and MPEA vapors simultaneously among various amines. Hereby, the study provides both promising accurate fluorescent multifunctional probe to AN and MPEA and new strategy for the construction of fluorescent sensors to organic amine vapors. Moreover, the new application of fluorescent exciplex is explored. Graphical abstract: Image 1 Highlights: F1 based on ready-made exciplex is firstly applied in organic amines detection. F1 can identify AN and MPEA vapors simultaneously among various amines. F1 can roughly distinguish aliphatic and aromatic amine vapors.